Usability and User Experience Analysis of Language Learning Applications with Augmented Reality Technology - Hendrawan, Satya Arisena; Putra, Haris Satria; Loebis, Iin Almeina; Fitriyasari, Maliatul; Basri, Hasan (Journal International of Lingua and Technology, 2025)
The integration of Augmented Reality (AR) technology into language learning applications has become increasingly popular due to its potential to enhance user engagement and improve learning outcomes. However, the usability and user experience (UX) of such applications are critical factors that determine their effectiveness. This study explores the usability and UX of language learning applications utilizing AR technology, aiming to evaluate how these applications meet the needs and preferences of users, and how they influence learning efficiency. The research adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews with users who have engaged with AR-based language learning applications. Participants were asked to assess the usability aspects, such as ease of navigation, user interface design, and responsiveness, as well as their overall experience and satisfaction. The results show that users generally find AR-based language learning applications engaging and enjoyable, particularly for vocabulary acquisition and interactive learning activities. However, challenges related to technical issues, such as device compatibility and software glitches, were identified as barriers to a seamless experience. The study concludes that while AR has the potential to revolutionize language learning, further improvements in application stability, content design, and personalization are necessary to optimize usability and user satisfaction.